Comparison of the Dopant Effect and Sample Preparation Method on Y-123 Superconductors - Ozturk, O.; Nefrow, A. R. A.; Bulut, F.; Kurnaz, S.; Safran, S. (Springer Science and Business Media LLC, 2021)
The detailed comparison of the effects of Co and CoFe2O4 dopants and preparation methods (solid-state reaction method and sol–gel methods) have been studied on structural, electrical, superconducting, and mechanical properties of Y123 bulk superconductors. The doping amounts of Co and CoFe2O4 were chosen up to 0.10 wt. %. X-ray powder diffraction (XRD) method, temperature-dependent resistance measurement (R-T), and Vickers microhardness analyses were performed to characterize prepared samples. XRD analysis showed that all samples have Pmmm symmetry of orthorhombic crystal structure; intensities and width of the diffraction lines were affected by doping material, but, independent of the preparation method. Although all samples crystallize in orthorhombic structure and exhibit superconductivity behavior, with increasing doping rate the critical transition temperatures of the samples showed a significant decrease and broadened to superconducting temperature transition width. This is more evident in CoFe2O4-doped Y-123 samples produced by sol–gel method. As the applied force increased, it was observed that the microhardness values of the Co-doped samples increased while the CoFe2O4-doped samples decreased, regardless of the sample preparation method.
Keywords: Preparation methods of superconductors; Y-123 phase; Co and CoFe2O4 doping